(untitled) (Sains Humanika, 2024)
Nowadays, learning coding has become a highly demanded teaching method to apply basic skills such as programming and computational thinking (CT) in line with current technological developments. Malaysia also takes this issue into account by introducing a pre-coding program for early childhood education. Pre-coding is an activity that teaches the concept of coding which is looking at computational thinking (CT) such as problem solving, logical thinking and creative thinking without involving the use of digital devices. This is because pre-coding is seen as more appropriate to be implemented for children in line with their developmental level who are in dire need of exploring the real world through physical activity. Therefore, this study aims to identify the views of private kindergarten teachers on pre-coding in early childhood education. This teacher’s view is seen from the aspects of knowledge, awareness, interest and acceptance of the teacher about the pre-coding program in early childhood education. This study uses a quantitative research design with a cross-sectional survey method. A total of 144 private kindergarten teachers around the states of Perak, Selangor and Putrajaya were selected as the study sample. The research instrument uses a set of questionnaires to answer the research objectives by looking at the median value for each aspect. The findings of the study show that the median value is high for the aspects of knowledge, awareness, interest and acceptance of teachers about pre-coding for children. The study found that the median value of all four aspects is equal to a value of 4. Therefore, the implementation of the pre-coding program is very important to be introduced and implemented in the early teaching and learning of children to help children acquire new basic skills in line with the development of the world of technology.